Schloß Rötha und die Freiherren von Friesen - Friesen-Rötha, Heinrich von (Sächsischer Heimatschutz, 1941)
Betr.: Erwähnt Architekt Bodenstein, Gemälde v. Jan de Perre, Samuel Bottschild, L. Cranach d. J., Antoine Pésne, L. de Silvestre, A. Graff u.a.